Altered Left Ventricular Ion Channel Transcriptome in a High-Fat-Fed Rat Model of Obesity: Insight into Obesity-Induced Arrhythmogenesis - Reza Ashrafi; Marianne Yon; Lucy Pickavance; Joseph Yanni Gerges; Gershan Davis; John Wilding; Kun Jian; Henggui Zhang; George Hart; Mark Boyett (Hindawi Limited, 2016)
Introduction. Obesity is increasingly common and is associated with an increased prevalence of cardiac arrhythmias. The aim of this study was to see whether in obesity there is proarrhythmic gene expression of ventricular ion channels and related molecules. Methods and Results. Rats were fed on a high-fat diet and compared to control rats on a normal diet (n=8). After 8 weeks, rats on the high-fat diet showed significantly greater weight gain and higher adiposity. Left ventricle samples were removed at 8 weeks and mRNA expression of ion channels and other molecules was measured using qPCR. Obese rats had significant upregulation of Cav1.2, HCN4, Kir2.1, RYR2, NCX1, SERCA2a, and RYR2 mRNA and downregulation of ERG mRNA. In the case of HCN4, it was confirmed that there was a significant increase in protein expression. The potential effects of the mRNA changes on the ventricular action potential and intracellular Ca2+ transient were predicted using computer modelling. Modelling predicted prolongation of the ventricular action potential and an increase in the intracellular Ca2+ transient, both of which would be expected to be arrhythmogenic. Conclusion. High-fat diet causing obesity results in arrhythmogenic cardiac gene expression of ion channels and related molecules.